Comparison of Machine Learning Models for Prediction of Initial Intravenous Immunoglobulin Resistance in Children With Kawasaki Disease - Kuniyoshi, Yasutaka; Tokutake, Haruka; Takahashi, Natsuki; Kamura, Azusa; Yasuda, Sumie; Tashiro, Makoto (Frontiers in Pediatrics, 2020)
Background: We aimed to construct an optimal machine learning (ML) method for predicting intravenous immunoglobulin (IVIG) resistance in children with Kawasaki disease (KD) using commonly available clinical and laboratory variables. Methods: We retrospectively collected 98 clinical records of hospitalized children with KD (2–109 months of age). We found that 20 (20%) children were resistant to initial IVIG therapy. We trained three ML techniques, including logistic regression, linear support vector machine, and eXtreme gradient boosting with 10 variables against IVIG resistance. Moreover, we estimated the predictive performance based on nested 5-fold cross-validation (CV). We also selected variables using the recursive feature elimination method and performed the nested 5-fold CV with selected variables in a similar manner. We compared ML models with the existing system regardless of their predictive performance. Results: The results of the area under the receiver operator characteristic curve were in the range of 0.58–0.60 in the all-variable model and 0.60–0.75 in the select-model. The specificities were more than 0.90 and higher than those in existing scoring systems, but the sensitivities were lower. Conclusions: Three ML models based on demographics and routine laboratory variables did not provide reliable performances. Additional biomarkers are likely to be needed to generate an effective prediction model.